Evaluation the Performance of Al-wahdaa Project Drinking Water Treatment plant: A case Study in Iraq - Ali A Mohammed; Alaa A. Shakir (Institute of Advanced Engineering and Science, 2012)
Al-wahdaa project drinking water treatment plant has been playing a vital role in supplying drinking water to Baghdad city since 1942s. It was designed with a design capacity 68000 m3/d So that it can cover the needs of the public properly. However, the fatal circumstances which have recently hit Baghdad city represented by wars and terrorist operations have considerably resulted in a significant deterioration in the quality of Al-wahdaa project water treatment plant in the early of 2005s and 2006s. Furthermore, the failure of the equipments and the deficiency of the crew of the power plant have dramatically caused a shortage in the efficiency of the plant. Therefore, this work is the earliest attempt in addressing the problem of this plant. In this study, the removal efficient of the filtration, sedimentation will be addressed as well as the turbidity during three years of investigation. It was found that the average value of the removal of the sedimentation basin was about (46%) and the ( R2 0.902) which is obviously low due to the absence of the permanent maintenance and the continuous clean out for the sedimentation basin. The removal efficiency of filtration basin was as high as (75%) and the( R2 0.445) comparatively with the removal efficiency of the sedimentation basin .The turbidity magnitudes were slightly oscillated along the study period since there has been shortage in the efficiency of sedimentation basin, it is then peaked at rainy season with about (18 NTU). The Total Dissolved Solids (often abbreviated TDS) was high but it may fall within the Limitations, it is interesting to note that it was highly increased at January due to the high turbidity discharge